Genetic variants of genes involved in thiopurine metabolism pathway are associated with 6-mercaptopurine toxicity in pediatric acute lymphoblastic leukemia patients from Ethiopia - Awol Mekonnen Ali; Haileyesus Adam; Daniel Hailu; Ephrem Engidawork; Rawleigh Howe; Teferra Abula; Marieke J. H. Coenen (Frontiers Media S.A., 2023)
Introduction: Genetic variation in the thiopurine S-methyltransferase (TPMT) gene by and large predicts variability in 6-mercaptopurine (6-MP) related toxicities. However, some individuals without genetic variants in TPMT still develop toxicity that necessitates 6-MP dose reduction or interruption. Genetic variants of other genes in the thiopurine pathway have been linked to 6-MP related toxicities previously.Objective: The aim of this study was to evaluate the effect of genetic variants in ITPA, TPMT, NUDT15, XDH, and ABCB1 on 6-MP related toxicities in patients with acute lymphoblastic leukemia (ALL) from Ethiopia.Methods: Genotyping of ITPA, and XDH was performed using KASP genotyping assay, while that of TPMT, NUDT15, and ABCB1 with TaqMan® SNP genotyping assays. Clinical profile of the patients was collected for the first 6 months of the maintenance phase treatment. The primary outcome was the incidence of grade 4 neutropenia. Bivariable followed by multivariable cox regression analysis was performed to identify genetic variants associated with the development of grade 4 neutropenia within the first 6 months of maintenance treatment.Results: In this study, genetic variants in XDH and ITPA were associated with 6-MP related grade 4 neutropenia and neutropenic fever, respectively. Multivariable analysis revealed that patients who are homozygous (CC) for XDH rs2281547 were 2.956 times (AHR 2.956, 95% CI = 1.494-5.849, p = 0.002) more likely to develop grade 4 neutropenia than those with the TT genotype.Conclusion: In conclusion, in this cohort, XDH rs2281547 was identified as a genetic risk factor for grade 4 hematologic toxicities in ALL patients treated with 6-MP. Genetic polymorphisms in enzymes other than TPMT involved in the 6-mercaptopurine pathway should be considered during its use to avoid hematological toxicity.